Development of an Ergonomic Based Adaptive Walker Design to Optimize Walking Mobility in the Elderly - Novia Pramesti Dwi Cahyani; Eko Wahyu Abryandoko; Amalia Ma’rifatul Maghfiroh (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2026)
The increasing elderly population has led to a higher prevalence of mobility limitations associated with reduced muscle strength, musculoskeletal disorders, and postural instability. Conventional walkers often fail to accommodate anthropometric variations and shock absorption needs, resulting in non-neutral postures and elevated ergonomic risk. This study developed an ergonomics-based adaptive walker integrating an adjustable handle mechanism and spring-based shock absorption. A pre- and post-intervention experimental approach involving five elderly participants was conducted using the Rapid Upper Limb Assessment (RULA) method. Initial RULA scores ranged from 5 to 7, indicating high to very high-risk levels. After using the adaptive walker, the scores decreased to 2–5, representing a 44.83% reduction in the average risk level. Improvements were observed in neck, trunk, and wrist posture, indicating enhanced ergonomic alignment and walking stability.